The Morning Literacy Program as an Effort to Strengthen the Reading Culture and Improve the Reading Skills of Madrasah Ibtidaiyah Students - Ain, Nafilatul; Marfuah, Siti; Karim, Abdul; Omiwole, Joseph Lere; Dasuki, Moh. (EDUCARE: Journal of Primary Education, 2025)
This study examines the low reading ability of students, the lack of teacher assistance in literacy programs, and the limited parental support for school literacy initiatives. The research method used in this study is qualitative. The type of research is field research. The study focuses its population on all students at the elementary madrasah, with research subjects including the principal, classroom teachers, and students. Data collection techniques used in this study include observation, interviews, and documentation. The type of observation employed is participatory, and the interviews are semi-structured. Documentary data was obtained through photos and videos taken during activities. The collected data was analyzed using the Miles and Huberman model, which consists of three stages: data reduction, data presentation, and conclusion drawing. The researcher validated the data using triangulation techniques. The results of this study indicate that there are three key approaches to improving students' reading skills in madrasah ibtidaiyah: a) teachers should use interactive and enjoyable strategies, b) teachers should engage in training on models and media that are attractive, while also providing supporting facilities such as libraries and reading corners, and c) parents should be involved in the school literacy program by providing interesting books at home and participating in family reading programs. This research contributes to strengthening teaching strategies, providing adequate facilities, and enhancing parental involvement to improve students' literacy skills in madrasah ibtidaiyah.